About the future role of software in the product - Henning Skirde; Robert Steinert (The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 25, 2018)
Product development is shifting towards realizing an extended scope of product functions in software. This leads to new challenges in terms of a methodological integration and synchronization of different development disciplines. This paper provides insights on how to systematically manage the harmonization of traditional development disciplines with agile software development based on an integrated data model. To achieve this, the traditional product data model is extended to a seamless system data model that covers - based on a common function structure - the product itself but also services induced by digitalization and infrastructure backends.
urn:nbn:de:gbv:830-88223396; 10419/209194; https://econpapers.repec.org/RePEc:zbw:hiclpr:25
Keywords: 650; Product Data Model METUS; Software Development; Agile and SCRUM; Harmonization; Digitilization